A PRELIMINARY INVESTIGATION TO ABUI LANGUAGE PROVERBS: TYPES, MEANINGS AND FUNCTIONS - Ambrosius Mikael Atalo; Novriani Rabeka Manafe; John Wem Haan (Academic Journal of Educational Sciences, 2020)
Considering the significance of proverbs in Abui communities in Alor island, this study aimed at 1) identifying the types of proverbs found in Abui language, 2) discovering the meaning conveyed by the proverbs and 3) investigating the functions served by the proverbs. The research employed qualitative case study by conducting the in-depth interview with five informants from West Welai Village, Teluk Mutiara Sub district, Alor Regency. The data were collected by using open ended questions. The data were then translated and transcribed to be analyzed by using thematic analysis. The findings and discussion led to three conclusions. First, there were thirty proverbs found in Abui language which consisted of twelve aphorism (40%), eleven idioms (36,67%) and seven parables (23,33%). Second, the majority of the proverbs (80%) conveyed proverbial while only six proverbs (20%) expressed idiomatic meaning. Lastly, regarding function, twelve proverbs (40%) in Abui language served as advices, nine of them showed the notion of sarcasm (30%), five proverbs gave warnings (16,67%) and the rest functioned as expressions (13,33%).